Achieving renewable energy targets: The impact of residential solar PV prosumers in Indonesia - janti Gunawan; Thasya Alifia; Kym Fraser (International Journal of Sustainable Energy Planning and Management, 2021)
Indonesia, like many countries, has committed to reducing its greenhouse gas (GHG) emissions. To do this the country needs to move from its current high reliance on non-renewable energy sources to renewable sources of energy. The issue is significant for Indonesia as the country is the 4th largest contributor to global CO2 emissions. The country has abundant sources for energy and one of these sources is the potential for solar energy. Therefore, the country has set ambitious renewable energy targets based on the potential supply of solar energy. With domestic residential consuming up to 43% of total electricity consumption, the Government has targeted homeowners to install solar rooftop and become residential solar PV prosumers. However, a recent energy evaluation report indicates that the country’s progress is very slow and it is highly likely that renewable energy goals will not be achieved. This study conducted an online survey of a small sample of regular electricity subscribers and residents who have installed solar rooftop in the hope of gaining a better understanding of various issues and factors which could be impeding the growth of residential solar. Some of areas the study explored included the level of knowledge and awareness of solar energy, initiatives for homeowners, policy on net-metering and feed-in tariff, and areas of concern related to economic, environmental, and technological factors. While many countries are struggling to shift to greener energy generation and consumption, in Indonesia’s case, the country has its own unique set of challenges being the energy generation and distribution is centralised, state-owned, with an inflexible energy pricing system. Hence, energy management in Indonesia could benefit from becoming more market focused and transparent, while increasing technology adoption with hybrid community partnerships, including a mix of private and government ownership. A discussion on policy implications and suggestions for improvements can be found at the end of this paper.